Does it matter what you call it? A randomized trial of language used to describe palliative care services - Maciasz, R. M.; Arnold, R. M.; Chu, E.; Park, S. Y.; White, D. B.; Vater, L. B.; Schenker, Y. (Supportive care in cancer, 2013)
Introduction Integration of palliative care into oncology practice remains suboptimal. Misperceptions about the meaning of palliative care may negatively impact utilization. Purpose We assessed whether the term and/or description of palliative care services affected patient views. Methods 2x2 between-subject randomized factorial telephone survey of 169 patients with advanced cancer. Patients were randomized into one of four groups that differed by name (supportive care vs. palliative care) and description (patient-centered vs. traditional). Main outcomes (0–10 Likert scale) were patient understanding, impressions, perceived need, and intended use of services. Results When compared to palliative care, the term supportive care was associated with better understanding (7.7 vs. 6.8; p = 0.021), more favorable impressions (8.4 vs. 7.3; p = 0.002), and higher future perceived need (8.6 vs. 7.7; p = 0.017). There was no difference in outcomes between traditional and patient-centered descriptions. In adjusted linear regression models, the term supportive care remained associated with more favorable impressions ( p = 0.003) and higher future perceived need ( p = 0.022) when compared to palliative care. Conclusions Patients with advanced cancer view the name supportive care more favorably than palliative care. Future efforts to integrate principles of palliative medicine into oncology may require changing impressions of palliative care or substituting the term supportive care.